Partisipasi Petani Dalam Program Gerakan Penerapan Pengelolaan Tanaman Terpadu Padi Di Kecamatan Kalasan Kabupaten Sleman - Octaviany Valentina Simanjuntak; Subejo Subejo; Roso Witjaksono (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2016)
GP-PTT program aims to increase rice production that is focused on the area of crops with the assistance of government facilities. As for the facilities or assistance given by the government that is seed, means of production, row planting system (legowo), and group meetings. This research was conducted in Kalasan, Sleman in order to (1) know the extent of farmer participation in the program GP-PTT rice in sub-district of Kalasan in 2015(2) know the factors related to the farmer participation in the GPPTT program in Kalasan. The method used in this research was descriptive by survey techniques. Selection of area sample was conducted purposively, while sampling farmers was conducted by simple random sampling. The total of respondents were 60 farmers. The analytical method used was the proportion test, chi-square analysis, and gamma test. The results of the research showed that the level of farmer participation in the program of GP-PTT was considered high with 71.13% initiation participation, 77.29% participation legitimacy, and 93.61% execution participation. Education is a factor that has a rather strong positive relationship with farmers’ participation in the GP-PTT. Attitude and motivation are factors that hold a strong positive relationship with farmers’ participation in GP-PTT. Factors that have no relation with farmers’ participation in that program are age, the role of educator, chairman of farmer group, and the role of local military staff.